Exploring the Role of Theatre in Enhancing English Vocabulary Acquisition: A Conceptual Analysis - Rahmadhanti, Novita Nur; Sulistyani, Ummi Nur Laila (Journal of English Language and Education, 2025)
This conceptual study explores how theatre can enhance English vocabulary acquisition in second and foreign language contexts. While vocabulary is widely recognized as a foundational component of language proficiency, traditional instruction often overlooks the affective and embodied dimensions of learning. Grounded in Kolb`s Experiential Learning Theory and Krashen`s Second Language Acquisition Theory, the study examines how theatrical practices such as role-play, dramatization, and improvisation can foster emotionally engaging and socially interactive learning environments that promote meaningful vocabulary learning. Using a library-based methodology, the research analyzes literature published between 2015 and 2025. Findings show that theatre creates an emotionally supportive environment, facilitates embodied vocabulary learning and enhances learners’ ability to acquire vocabulary in contextualized ways. The study concludes that although there are challenges in the implementation, theatre can be a transformative tool for deepening learners` vocabulary knowledge and communicative competence when systematically integrated into English language education.